2005
DOI: 10.1002/jcb.20548
|View full text |Cite
|
Sign up to set email alerts
|

Subnuclear targeting of Runx1 Is required for synergistic activation of the myeloid specific M‐CSF receptor promoter by PU.1

Abstract: Many types of acute myelogenous leukemia involve chromosomal translocations that target the C-terminus of Runx1/AML1 transcription factor, a master regulator of hematopoiesis. The C-terminus of Runx1/AML1 that includes the nuclear matrix targeting signal (NMTS) is essential for embryonic development, hematopoiesis, and target gene regulation. During the onset and normal progression of hematopoiesis, several lineage-specific factors such as C/EBPalpha and PU.1 interact with Runx1 to regulate transcription combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 64 publications
1
30
0
Order By: Relevance
“…Taking together, our data strongly suggest that ThGM cells are distinct from the known phenotypes of Th1, Th2, Th17, or Treg cells. As the transcription factors NFATc1, AP-1 and RUNX-1 were reported to bind to the promoter of GM-CSF and regulate its production, 37,38 we examined these genes and found that NFATc1, AP-1, and RUNX-1 were expressed in ThGM cells, although at different levels (Supplementary Figure S6). This result indicates that these genes may be involved in ThGM differentiation, although further investigation on the molecular level is still required to clarify the mechanism of the transcription factor.…”
Section: Generation and Characterization Of Thgm Cellsmentioning
confidence: 99%
“…Taking together, our data strongly suggest that ThGM cells are distinct from the known phenotypes of Th1, Th2, Th17, or Treg cells. As the transcription factors NFATc1, AP-1 and RUNX-1 were reported to bind to the promoter of GM-CSF and regulate its production, 37,38 we examined these genes and found that NFATc1, AP-1, and RUNX-1 were expressed in ThGM cells, although at different levels (Supplementary Figure S6). This result indicates that these genes may be involved in ThGM differentiation, although further investigation on the molecular level is still required to clarify the mechanism of the transcription factor.…”
Section: Generation and Characterization Of Thgm Cellsmentioning
confidence: 99%
“…Commonly, M-CSF secreted by cells, binds to its transmembrane receptor which leads to the transduction of the signal onto the target cell; then the M-CSF-receptor complex is internalized after accomplishing its function and degraded; therefore, M-CSF is usually not found in the cells. However, recent studies have shown that M-CSF can be expressed at a high level in the cytoplasm and nuclei of some kinds of malignant tumors [23][24][25]. The process is associated with enhanced tumor cells' movement and invasion, resulting in an unfavorable prognosis, which suggests that intracellular expression of M-CSF may have some specific action.…”
Section: Discussionmentioning
confidence: 99%
“…This structural model was used as the foundation for mutagenesis studies that targeted a putative protein/protein interface composed of basic and aromatic residues in the two loops to define subnuclear trafficking specificity at single amino acid resolution (Zaidi et al, 2006). We observed that a highly conserved Y motif in the C-terminal loop is critical for subnuclear targeting of Runx (AML) and transcriptional control (Li et al, 2005;Zaidi et al, 2006Zaidi et al, , 2001.…”
Section: Molecular and Structural Determinants Of Subnuclear Targetinmentioning
confidence: 99%